Professionalization of the DGPs Structures Professionalisierung der DGPs-Strukturen - Vaterrodt, Bianca; Abele-Brehm, Andrea; Gollwitzer, Mario; Stemmler, Gerhard (Psychologische Rundschau, 2024)
This article describes the main steps in the professionalization of the German Psychological Society (DGPs) regarding its structures, administration, collaborations, and public relations work. In addition to describing relevant changes to the statutes that led to the founding of the specialist groups and the Faculty Day of Psychology, the establishment of the DGPs office in Berlin, and the founding of the TransMit Centre for Scientific-Psychological Services, it chronicles the expansion of national and international collaborations. The professionalization of public relations and internal communication has benefited particularly from digitalization.
CRIS-Team Scopus Importer:2024-04-26
Keywords: academic society; development; DGPs; German Psychological Society; professionalization; psychological society; statutes